Phylogenetic analysis in silico of orchid species Dendrobium based on rbcl marker - Febriansyah, Muhammad; Mahfut (Tropical Genetics, 2024)
Dendrobium is one of the genera of the third largest Orchidaceae family which reaches about 1184 species in the world. In Indonesia, this genus of orchids is a wealth of genetic resources that are abundant in the Eastern region, such as Papua and Maluku. These genetic resources have not been optimally utilized as elders in crossbreeding to produce offspring that have characteristics according to what consumers want. Due to the limitations of these morphological characteristics, another character is needed that can support the systematics of orchids, namely molecular characters. Plant kinship analysis can use molecular characters in the form of DNA strands that can overcome the weaknesses of morphological data that are known to have limitations and tend to be influenced by the environment. This study aims to analyze the kinship of several types of Dendrobium based on the rbcL gene and add to the basic data source of germplasm from the genus Dendrobium. The samples used were nucleotide sequences of 11 nucleotide sequences consisting of 10 types of Dendrobium (D. anosmum, D. jinghuanum, D. catenatum, D. nobile, D. jenkinsii, D. pahangense, D. nobile, D. pulchellum, D. fimbriatum, and D. pulchellum) which is used as an in group and 1 species of the genus Phalaenopsis namely Phalaenopsis equestris which is used as an outgroup. The results of Dendrobium kinship analysis with an in silico based rbcL gene molecular approach show that species in the same genus are not necessarily closely related. The species that is a member of the out group is Phalaenopsis equestris,. Phalaenopsis equestris forms its own tree branches, while the other 10 species are on the same phylogeny tree branches.